Wastewater-Based Epidemiology as an Early Warning System for the Spreading of SARS-CoV-2 and Its Mutations in the Population - Mackuľak, Tomáš; Gál, Miroslav; Špalková, Viera; Fehér, Miroslav; Briestenská, Katarína; Mikušová, Miriam; Tomčíková, Karolína; Tamáš, Michal; Butor Škulcová, Andrea (International journal of environmental research and public health, 2021)
New methodologies based on the principle of "sewage epidemiology" have been successfully applied before in the detection of illegal drugs. The study describes the idea of early detection of a virus, e.g., SARS-CoV-2, in wastewater in order to focus on the area of virus occurrence and supplement the results obtained from clinical examination. By monitoring temporal variation in viral loads in wastewater in combination with other analysis, a virus outbreak can be detected and its spread can be suppressed early. The use of biosensors for virus detection also seems to be an interesting application. Biosensors are highly sensitive, selective, and portable and offer a way for fast analysis. This manuscript provides an overview of the current situation in the area of wastewater analysis, including genetic sequencing regarding viral detection and the technological solution of an early warning system for wastewater monitoring based on biosensors.
Keywords: mutace; Wastewater; Humans; lidé; epidemiologie odpadních vod; SARS-CoV-2; odpadní vody; Wastewater-Based Epidemiological Monitoring; Mutation; COVID-19; Sewage; odpadní voda